3D porous metal–organic framework for selective adsorption of methane over dinitrogen under ambient pressure. Issue 100 (30th November 2018) - Kivi, Charlie E.; Gelfand, Benjamin S.; Dureckova, Hana; Ho, Ha T. K.; Ma, Cindy; Shimizu, George K. H.; Woo, Tom K.; Song, Datong
Abstract : A new porous Ni-MOF displays high selectivity and working capacity for CH4 adsorption over N2 under ambient conditions. Abstract : We report a highly porous 3D metal–organic framework (MOF) that shows potential for coal mine methane (CMM) capture.